(untitled) (Proceedings of Southern Federal University. Philology, 2022)
DOI 10.18522/1995-0640-2022-4-176-185 The paper presents the stages of work on the block "Modern Foreign Literature" as part of the discipline "History of Foreign Literature". The main trends in Western European and American prose are highlighted. The following genres are characterized: anti-utopia, transformer novel, myth novel, philological novel; phenomena: neorealism, seterature (in particular, fanfiction). The specificity of fantastic literature at the present stage is determined. Common features for the literature of the late 20th – early 21st centuries are traced: intertextuality, hypertextuality, openness, polyvariability of ideas, mythologism. Key words: postmodernism, genre syncretism, collage, explicit / implicit citation, mythologism, author’s absence effect, text openness.